2024
DOI: 10.1371/journal.pone.0300362
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in non-alcoholic fatty liver disease: A cross-cultural study between Spain and the United Kingdom

Jesús Funuyet-Salas,
Agustín Martín-Rodríguez,
María Ángeles Pérez-San-Gregorio
et al.

Abstract: Background It is unclear what biopsychosocial factors influence the impact of NAFLD on health-related quality of life (HRQoL), and if these factors are equally important predictors between different nationalities. Methods HRQoL (CLDQ) was measured in both Southern European (Spain, n = 513) and Northern European (United Kingdom -UK-, n = 224) cohorts of patients with NAFLD in this cross-sectional study. For each cohort, participant data were recorded on histological grade of steatohepatitis, stage of fibrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(117 reference statements)
0
1
0
Order By: Relevance
“…In patients with chronic liver disease, fatigue was associated with neuroinflammation and altered neurophysiological mechanisms. 9 Previous research found that hepatic inflammation through vagal afferent and uptake of pro-inflammatory cytokines enhanced brain’s sense of fatigue. 10 NAFLD was considered to be an inflammatory response-related disease, and inflammatory burden and metabolic abnormalities may be involved in the development of fatigue in NAFLD patients.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic liver disease, fatigue was associated with neuroinflammation and altered neurophysiological mechanisms. 9 Previous research found that hepatic inflammation through vagal afferent and uptake of pro-inflammatory cytokines enhanced brain’s sense of fatigue. 10 NAFLD was considered to be an inflammatory response-related disease, and inflammatory burden and metabolic abnormalities may be involved in the development of fatigue in NAFLD patients.…”
Section: Introductionmentioning
confidence: 99%